2007
DOI: 10.1373/clinchem.2006.079327
|View full text |Cite
|
Sign up to set email alerts
|

MESOMARK™: A Potential Test for Malignant Pleural Mesothelioma

Abstract: Background: Soluble mesothelin-related peptides (SMRP) have been reported to be potential biomarkers for malignant pleural mesothelioma (MPM). We report analytical and preliminary clinical studies of MESOMARK TM , a quantitative assay for SMRP. Methods: The MESOMARK assay is a 2-step immunoenzymatic assay in an ELISA format with a 6-point calibration curve (0 -32 nmol/L). We assessed analytical imprecision, analyte stability, and analytical interferences. We measured SMRP by this assay in 409 apparently health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
124
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 15 publications
13
124
2
Order By: Relevance
“…Higher clinical stages of mesothelioma (stages II and III-IV) are associated with higher SMRP concentrations 6,58,69,71 . Other data suggest that serum mesothelin levels increase as the tumor grows 53,70,71 . On the other hand, surgical tumor reduction is followed by a decrease in SMRP levels 6,35,68 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Higher clinical stages of mesothelioma (stages II and III-IV) are associated with higher SMRP concentrations 6,58,69,71 . Other data suggest that serum mesothelin levels increase as the tumor grows 53,70,71 . On the other hand, surgical tumor reduction is followed by a decrease in SMRP levels 6,35,68 .…”
Section: Discussionmentioning
confidence: 99%
“…But recent studies recommend that SMRP should not be used in the screening for mesothelioma in asbestosexposed persons 3,61 . Numerous studies have been performed to assess the utilization of mesothelin in the diagnosis of mesothelioma, reporting a sensitivity of 50-84% and specificity of 72-95% and statistically significantly higher SMRP levels in mesothelioma as compared with healthy exposed individuals or those with benign asbestos-induced conditions 30,31,35,55,[68][69][70][71][72] . Recent meta-analysis reported a sensitivity and specificity of SMRP for mesothelioma of 32-64% and 88-100%, respectively 73,74 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data available for the second assay is limited and it is difficult to say if this assay is better than the Mesomark™ kit which has been used by the majority of investigators and showed a very good reproducibility and precision with little constraints concerning sample storage or interference with other substances [47][48][49]. A head to head comparison of the two kits would be useful but is presently unavailable.…”
Section: Mesothelinmentioning
confidence: 99%